Manipulation of chitosan binding on the polyethylene terephthalate (PET) surface and study of coatings on poultry meat shelf life-time - Tkavc, Tina (visokošolska dela, 2014)
The aim of this study was to activate inert PET surfaces in order to introduce the surfaces% carboxyl groups and to obtain its hydrophilic character, which was important for the chitosan bonding to it. Films where chitosan was attached to the PET could be used as active packaging material for food like fresh poultry meat. For PET activation two advanced and environmentally friendly techniques were used: 1) O2 plasma activation; and 2) CO2 plasma activation. Differently treated PET foils deposited on Au quartz crystals (model studies - adsorption and desorption) and real films were characterized. Later on, real films were studied in the terms of carboxylic/amino group content, hydrophobic/hydrophilic character, surface composition and adsorption/desorption of chitosan onto/from the surface. Results clearly showed that the use of both surfaces% activation processes increased the ability of PET foils to adsorb chitosan, but CO2 plasma gave a higher concentration of carboxyl groups on the PET surface and consequently, due to the chemical bonding the chitosan layers were more stable. Even though CO2 plasma pre-treated PET foils gave better results during the experimental work, we could not avoid layer by layer adhesion of chitosan which resulted in non-bound molecules. Pre-treated foils and with chitosan functionalized foils were tested preliminarily with ASTME E1 (2002) microbiological tests. Functionalized CO2 plasma pre-treated foils gave the broadest spectra of antimicrobial activity, and therefore they were chosen for further microbiological analyses, where chitosan`s influence on inoculated poultry models towards selected standard strains, typical for poultry meat, was being tested. By determining the MIC (minimal inhibitory concentration) for selected microorganisms we have proven, that chitosan possesses antimicrobial properties at low concentrations. During the transfer of the experiment to a larger scale (food models, which are a very complex environment), it has been shown that on PET bonded chitosan did not have the inhibitory effect to that extent, with the exception of Staphylococcus aureus, as was expected. Similar results were expressed using both these methods: Colony count technique and real-time PCR. In the end, the organoleptic properties of the chicken models exposed to foils have shown that chitosan changes the color and taste of meat immediately after exposure, but samples were staying edible longer. Therefore, functionalized PET, which has an inhibitory influence towards variety of microorganisms, may be applied as an active packaging system for poultry meat after some optimization of the coating procedure in binding chitosan onto the PET surfaces.
Keywords: adsorption-desorption kinetics; antimicrobial packaging; chitosan; Disertacije; Hitozan; kinetika adsorpcije; kinetika desorpcije; microbiological tests; mikrobiološko testiranje; PET; Polietilen tereftalat; protimikrobna embalaža